Impact of sublethal levels of mercury on glycogen and selected respiratory enzymes in Heteropneustesfossilis and role of water hyacinth in reduction of Hg toxicity - James, R; Pattu, V Jancy; Devakiamma, G; Sampath, K (Indian Journal of Fisheries, 2011)
Mercury adversely affects various physiologicaland biochemical functions of fish(Snarski and Olson 1982; Muthukrishnan etal. 1986). Water hyacinth, Eichhornia erassipes,has been reported to have the capabilityof absorbing and removing someheavy metalsfrom poUuted water bodies (Wolverton andMcDoiaM 1975; Chigbo et al. 1982). However,studies on utilization of aquiUic plantsfcff Ae reduction of mercury toxicity to fishare lacking. Tliis study rqx)its die sublethaleffects of morury on glycogen and selectedrespirat(Â»y enzymes in Hetert^mustes fossilisand the role of wato- hyacindi in reducingthe metal toxicity.